A high-throughput drug screening identifies luteolin as a therapeutic candidate for pathological cardiac hypertrophy and heart failure - Wang, Zhenya; Shi, Wei; Wu, Taibo; Peng, Tian; Wang, Xiaoming; Liu, Shuaiyang; Yang, Zifeng; Wang, Jia; Li, Peng-Long; Tian, Ruifeng; Hong, Ying; Yang, Hailong; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background Pathological cardiac hypertrophy is commonly resulted from sustained pressure overload and/or metabolic disorder and eventually leads to heart failure, lacking specific drugs in clinic. Here, we aimed to identify promising anti-hypertrophic drug(s) for heart failure and related metabolic disorders by using a luciferase reporter-based high-throughput screening. Methods A screen of the FDA-approved compounds based on luciferase reporter was performed, with identified luteolin as a promising anti-hypertrophic drug. We systematically examined the therapeutic efficacy of luteolin on cardiac hypertrophy and heart failure in vitro and in vivo models. Transcriptome examination was performed to probe the molecular mechanisms of luteolin. Results Among 2,570 compounds in the library, luteolin emerged as the most robust candidate against cardiomyocyte hypertrophy. Luteolin dose-dependently blocked phenylephrine-induced cardiomyocyte hypertrophy and showed extensive cardioprotective roles in cardiomyocytes as evidenced by transcriptomics. More importantly, gastric administration of luteolin effectively ameliorated pathological cardiac hypertrophy, fibrosis, metabolic disorder, and heart failure in mice. Cross analysis of large-scale transcriptomics and drug-target interacting investigations indicated that peroxisome proliferator activated receptor γ (PPARγ) was the direct target of luteolin in the setting of pathological cardiac hypertrophy and metabolic disorders. Luteolin can directly interact with PPARγ to inhibit its ubiquitination and subsequent proteasomal degradation. Furthermore, PPARγ inhibitor and PPARγ knockdown both prevented the protective effect of luteolin against phenylephrine-induced cardiomyocyte hypertrophy in vitro. Conclusion Our data clearly supported that luteolin is a promising therapeutic compound for pathological cardiac hypertrophy and heart failure by directly targeting ubiquitin-proteasomal degradation of PPARγ and the related metabolic homeostasis.